Dreamweaver MX 2004 : the missing manual. - Sawyer McFarland, David, ....- (Beijing : O'Reilly, 2004)
Samenvatting:Macromedia's Dreamweaver MX 2004 is the leading software tool for thecreation of Web sites and other HTML interfaces. It's remarkably capable,able to deal intelligently with everything from fonts and images toJavaScript for client-side data validation and embedded Java applets. Inmost cases, Dreamweaver will save you time over hand-coding--and yieldbetter-looking pages to boot. The program's learning curve, though, isn'ttrivial. That's why Dreamweaver MX 2004: The Missing Manual is worthhaving on hand as you learn to use Dreamweaver, and worth keeping withinreach as you tackle increasingly difficult Web development work.David McFarland wrote this book, but the influence of esteemed serieseditor David Pogue is obvious in the careful coverage of features andfrequent touches of humor (books about applications can be whanginglydull; the books in Pogue's Missing Manual series consistently manage toavoid this problem while maintaining comprehensiveness). The two mentreat Dreamweaver's numerous features (and the even more numerous ways ofputting them to use) cleverly, with a combination of procedures and sideinformation that clarifies many oddball situations as well asstraightforward conditions. --David WallTopics covered: How to create HTML (XHTML and CSS, strictly speaking)documents using Macromedia Dreamweaver MX 2004. In addition to the basicstuff (text, images, links, and frames), the book shows you how to buildforms for data submission and embed Flash movies and Java applets.There's also a lot of helpful emphasis on Dreamweaver's productivityfeatures, like snippet libraries and file transfer utilities. A specialsection shows you how to do some server-side work with databases.
Keywords: Elektronisch publiceren; Programmatuurontwikkeling; Www world wide web